2012
DOI: 10.1073/pnas.1120455109
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum erythrocyte membrane protein 1 domain cassettes 8 and 13 are associated with severe malaria in children

Abstract: The clinical outcome of Plasmodium falciparum infections ranges from asymptomatic parasitemia to severe malaria syndromes associated with high mortality. The virulence of P. falciparum infections is associated with the type of P. falciparum erythrocyte membrane protein 1 (PfEMP1) expressed on the surface of infected erythrocytes to anchor these to the vascular lining. Although var2csa, the var gene encoding the PfEMP1 associated with placental malaria, was discovered in 2003, the identification of the var/PfEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
422
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 242 publications
(450 citation statements)
references
References 55 publications
24
422
1
3
Order By: Relevance
“…The demonstration here of up-regulation of a subset of group A-like var genes in HBEC-5i-selected parasites fits well with a body of previous work on var gene transcription in P. falciparum clinical isolates as well as the companion article by Lavstsen et al (44). The majority of studies addressing the relationship between var genes and clinical disease have found an association between group A var gene transcription and severe malaria or CM (16)(17)(18)(19)51).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The demonstration here of up-regulation of a subset of group A-like var genes in HBEC-5i-selected parasites fits well with a body of previous work on var gene transcription in P. falciparum clinical isolates as well as the companion article by Lavstsen et al (44). The majority of studies addressing the relationship between var genes and clinical disease have found an association between group A var gene transcription and severe malaria or CM (16)(17)(18)(19)51).…”
Section: Discussionsupporting
confidence: 87%
“…4). In their companion articles, Avril et al (43) provide independent confirmation of the up-regulation of DC8 genes following selection on brain endothelial cells, and Lavstsen et al (44) show DC8 and DC13 genes to be highly differentially transcribed in patients with severe malaria compared with UM controls, confirming the clinical importance of DC8-and DC13-expressing parasites. DC8 genes were differentially transcribed in all clinical forms of severe malaria (CM, severe malarial anemia, and respiratory distress), consistent with our findings and those of Avril et al (43) that parasites selected for binding to HBEC-5i also could adhere to other primary endothelial cell types, giving the potential to sequester at multiple sites throughout the body in addition to the brain.…”
Section: Discussionmentioning
confidence: 95%
“…Transcription of group A genes, which are less diverse than the other groups, has been related to severe malaria in several studies (6)(7)(8)(9)(10)(11), which fits the restricted serological diversity of P. falciparum from patients with severe malaria and the relatively rapid acquisition of immunity to complicated disease (12)(13)(14). Particular subtypes of DBL and CIDR domains can be found in combination in short tandem domain cassettes (DCs) shared by many different parasite strains (15), and two such cassettes (DC8 and DC13) found in group A PfEMP1 proteins were recently implicated in the pathogenesis of cerebral P. falciparum malaria (16)(17)(18). The key event of this grave complication is accumulation of IEs in the cerebral microvasculature, and ICAM-1 has been suggested as an important receptor for IEs adhering in the brain (19)(20)(21).…”
mentioning
confidence: 75%
“…First, the PfEMP1s were arranged into groups A, B and C, depending on their chromosomal location and the domain types encoded [31]. Expression of a subset of PfEMP1s, which contain a specific set of domains, known as CIDRα1 domains, was associated with severe malaria or brain endothelial cell binding [32][33][34][35]. Later, CIDRα1 domains were found to bind to human EPCR [16], thereby preventing EPCR from interacting with its natural ligand, activated protein C [16,36] (Figure 1).…”
Section: Do Anti-disease Immunogens Have a Place In Future Malaria Vamentioning
confidence: 99%